2016
DOI: 10.1371/journal.pone.0149691
|View full text |Cite
|
Sign up to set email alerts
|

RNAi and Homologous Over-Expression Based Functional Approaches Reveal Triterpenoid Synthase Gene-Cycloartenol Synthase Is Involved in Downstream Withanolide Biosynthesis in Withania somnifera

Abstract: Withania somnifera Dunal, is one of the most commonly used medicinal plant in Ayurvedic and indigenous medicine traditionally owing to its therapeutic potential, because of major chemical constituents, withanolides. Withanolide biosynthesis requires the activities of several enzymes in vivo. Cycloartenol synthase (CAS) is an important enzyme in the withanolide biosynthetic pathway, catalyzing cyclization of 2, 3 oxidosqualene into cycloartenol. In the present study, we have cloned full-length WsCAS from Withan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…5 ). Previous reports show that CAS overexpression and silencing resulted in an increase and decrease of withanolide content respectively 24 . In endophyte-inoculated plants, increased expression of CAS , SMT and ODM were correlated with enhanced withanolides production.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…5 ). Previous reports show that CAS overexpression and silencing resulted in an increase and decrease of withanolide content respectively 24 . In endophyte-inoculated plants, increased expression of CAS , SMT and ODM were correlated with enhanced withanolides production.…”
Section: Discussionmentioning
confidence: 95%
“…Overexpression of squalene synthase ( SQS ), a key regulatory gene of withanolide biosynthesis in W. somnifera could increase the content of withaferin A and withanolide A in the leaves up to 4–4.5 fold 23 . Overexpression of cycloartenol synthase ( CAS ) in W. somnifera increased the withanolide content to the extent of 1.06 to 1.66 fold 24 . Use of cell suspension 25 , adventitious 26 , 27 , and hairy root culture 28 for improvement of withanolide production have also been tried.…”
Section: Introductionmentioning
confidence: 99%
“…According to the difference in the substituted groups of C-17 side chain, withanolides can be divided into two types; type A with a δ-lactone or δ-lactol and type B with γ-lactone or γ-lactol side chain [217]. Some recent investigations have identified putative regulatory and structural genes involved in withanolide biosynthesis [218][219][220][221].…”
Section: Withanolidesmentioning
confidence: 99%
“…This result corresponded to the DEUGs of the PtCAS genes after MeJA treatment. Similarly, Mishra et al [ 19 ] reported that transcript levels of the WsCAS ( Withania somnifera cycloartenol synthase) gene of the W. somnifera seedling, which contains a large amount of steroidal triterpene saponins, increased up to 1.65-fold after MeJA treatment. Taken together, these results suggest that the PtCAS genes may contribute to secondary steroidal triterpenoid biosynthesis as well as to phytosterols in P. tenuifolia .…”
Section: Resultsmentioning
confidence: 96%
“…It is likely that the PtCAS1 gene is constantly expressed to produce phytosterols and the PtCAS2 gene is responsible for the biosynthesis of steroidal compounds to protect themselves against changing or harsh environments such as pathogens coming into contact with flowers. In addition, CAS is activated to produce steroidal triterpenoids as secondary metabolites, like withanolide [ 19 ]. After 12 h of MeJA treatment on the seedlings of P. tenuifolia , the transcripts of the two CAS genes were higher than that of the control ( Figure 6 B).…”
Section: Discussionmentioning
confidence: 99%